BHAGAT DHANNA JI AND HIS CONTRIBUTION IN GURU GRANTH SAHIB - Kaur, Ravinder; Khandelwal , Jayanti Lal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Guru Granth Sahib, the holy scripture of Sikhism and the Eternal guru of the Sikhs, stands as a monumental text in the history of spiritual literature, embodying a wealth of philosophical wisdom, moral guidance and universal ideology. This article explores the role of Bhagat Dhanna in the Guru Granth Sahib and its significance as well. This article also tells us about the journey of transformation of a simple farmer into a great Bhakti Saint. The inclusion of Bhagat Dhanna’s bani or hymns in The Guru Granth Sahib by Guru Arjun Dev (5th Sikh Guru) reinforces the universal message of spiritual unity, brotherhood and the inclusive nature of the Sikh faith.